Geologic mapping of the AV-15 Rheasiliva quadrangle of asteroid 4 Vesta - White, Oliver L.; Yingst, R. Aileen; Berman, D.; Frigen, A.; Jaumann, R.; Le Corre, L.; Mest, S.; Pieters, C.; Preusker, Frank; Raymond, C.A.; Reddy, V.; Roatsch, Thomas; et al. (2012)
NASA’s Dawn spacecraft entered orbit of the inner main belt asteroid 4 Vesta on July 16, 2011, and is spending one year in orbit to characterize the geology, elemental and mineralogical composition, topography, shape, and internal structure of Vesta be-fore departing to asteroid 1 Ceres in late 2012. As part of the Dawn data analysis the Science Team is con-ducting geologic mapping of the surface, in the form of 15 quadrangle maps. This abstract reports results from the mapping of quadrangle Av-15, named Rheasilvia. Data: The base for mapping this quadrangle is a monochrome Framing Camera (FC) mosaic produced from the High Altitude Mapping Orbit (HAMO) data with a spatial resolution of ~70 m/pixel. This base is supplemented by a Digital Terrain Model (DTM) de-rived from Survey orbit data (Figure 1). Also used to support the mapping are FC color ratio images from the Survey orbit with a spatial resolution of ~250 m/pixel, slope and contour maps derived from the DTM, and Visible and InfraRed (VIR) hyperspectral images from the Survey and HAMO orbits with spatial resolutions of 700 and 200 m/pixel, respectively. Geologic Setting: Av-15 Rheasilvia Quadrangle covers the southern pole of Vesta and stretches north to 21°S. This quadrangle is dominated by the central mound complex of the Rheasilvia impact basin. The quad is heterogeneous spectrally, and in terms of color and albedo [1-4]; these heterogeneities were originally interpreted to stem from extrusive volcanic activity and impact. Imaging by the Hubble Space Telescope (HST) in 1994 and 1996 revealed a crater at the south pole that excavated ~1% of the asteroid's volume; the presence of a 1-μm absorption feature was interpreted as coarse-grained plutonic pyroxene or pos-sibly olivine in a differentiated upper mantle [5].